Relevansi Pendekatan Semantik Toshihiko Izutsu dalam Menafsirkan Al-Qur’an - Rahmat Soleh; Suwarno Suwarno; Ikrimah Retno Handayani (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2022)
The study of the Qur'an is not only an important concern for Muslims, butthe Qur'an has also attracted the attention of orientalists in interpreting it using variousapproaches, one of which is the semantic approach carried out by Thoshihiko Izutsu.This paper discusses the relevance of Toshihiko Izutsu's semantic approach ininterpreting the Qur'an. The method used in this paper is a literature researchmethodology by referring to writings related to the discussion theme. This paperconcludes that Toshihiko Izutsu's semantic approach is quite relevant to the needs ofcontemporary interpretation. Because Toshihiko contains a new view in the Qur'anicworld (weltanscuung) so that he can explain things that are sometimes complicated tobe simpler through explanations from a review of their relational meanings. In theend, this semantic approach can be used but not for all vocabulary in the Qur'an, thestudy must also be precise and in-depth, it cannot be arbitrary in understanding themeaning of a vocabulary in the Qur'an